SMART TECHNO PARENTING DALAM MEMBENTUK KARAKTER ANAK - syaifuddin syaifuddin syaifuddin; Hefniy Hefniy (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2019)
Digital technology as a whole is revolutionizing the way we do business, doing research, choosing entertainment, and even how to socialize. The emergence of digital technology is actually neutral, positive, and negative which can arise depending on its utilization. Parenting is a process of interaction between parents and children that are influenced by the culture and social institutions in which children are raised. The formation of children's characters requires an effective, applicable and productive methodology so that the expected goals can be achieved well. This research uses a qualitative research approach with a case study model. This research was conducted among lecturers at Nurul Jadid University, Paiton Probolinggo. Sources of data in this study consisted of primary sources and secondary sources. Data analysis techniques in this study include data collection, data reduction, data display and conclusion drawing. The implementation of smart techno parenting in shaping the character of children is to teach technology, impose limits on the use of technology, lead to educational games, learning activities and worship associated with learning to use technology. The implication is that children know about technology, children become disciplined in utilizing technology, make it easier to monitor children's attitudes and behaviour, train intellectual and religious intelligence, and increase children's worship and learning.